HUBUNGAN PENGETAHUAN REMAJA TENTANG COVID-19 DENGAN KEPATUHAN DALAM MENERAPKAN PROTOKOL KESEHATAN DI MASA NEW NORMAL - Dhonna Anggreni; Citra Adityarini Safitri (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2020)
Covid-19 is currently a serious world problem with the number of cases which are always increasing every day. Attacking everyone regardless of age or gender and has been categorized as a global pandemic. Even adolescents are not immune to covid infection 19. In Indonesia alone, the number of positive cases in September 2020 was 240,687 people with 9,448 deaths. The purpose of this study was to examine the relationship between adolescent knowledge about covid-19 and adherence to implementing health protocols in the new normal period. This type of research is an analytical study with a cross-sectional design. The independent variable of this study is adolescent knowledge. While the independent variable is compliance in implementing health protocols. The sample in this study were 111 people. The data were analyzed using the Sperman test statistical test. The results showed that there was no relationship between adolescent knowledge about Covid-19 and adherence to implementing health protocols. Many factors influence the degree of disobedience among adolescents, one of which is motivation or support from family members and themselves. It is hoped that the family can provide an example and motivation for adolescents to want to apply health protocols wherever they are